Polycentricity and multi-stakeholder platforms: Governance of the commons in India - ElDidi, Hagar; Rawat, Shivanyaa; Meinzen-Dick, Ruth S.; Chaturvedi, Rahul (International Food Policy Research Institute, 2021)
Commons governance is complex and polycentric, involving a range of actors, working at different scales with different concepts of ‘development’, and different types of power. Multi-stakeholder platforms (MSPs) have generated considerable attention as a way to address these tensions among multiple and overlapping decision-making centers operating on different administrative levels and scales. Yet establishing MSPs that effectively involve both community, government, and private sector actors is far from straightforward. This paper analyzes the Indian NGO Foundation for Ecological Security’s (FES) experience of strengthening polycentric governance through case studies of two MSPs in Gujarat and Odisha, at the block (subdistrict) level—a meso-level encompassing multiple communities situated around a commons landscape (hill range or small rivulet). By comparing local environments, institutional arrangements, stakeholder interactions, governance processes and the evolution of MSPs in the two states, it distills lessons on the tangible and intangible benefits of multi-stakeholder engagement, scale, and enabling conditions. We argue that the groundwork carried to build community level collective action supports effective polycentric governance of resources on the landscape level, especially through block-level MSPs that facilitate inter-community collaboration and learning, strengthening local voices and building trust between stakeholders over time. The cases also highlight that MSPs can evolve in different ways as the various actors interact and aim to influence the agenda. External actors like NGOs thus play an important role as facilitators and through mobilizing communities to help them claim their agency.